ANALISIS PENGELOLAAN PENYUSUNAN RENCANA KERJA DI BAGIAN PERENCANAAN Dan EVALUASI DINAS KESEHATAN KABUPATEN SLEMAN D.I.Y - Sri Wahyuning; Janna Prafika; Moh. Sholihin (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
Where the Health Office has the task of assisting the Regent in carrying out government affairs and auxiliary tasks in the health sector in carrying out its duties the Health Office has one of the functions, namely preparing a work plan. Therefore, we conducted a review and analysis related to the management of work plan preparation in the planning and evaluation section of the Sleman Regency Health Office, D.I.Y. The research was conducted using interviews, observation and documentation methods. Based on the results of the analysis and discussion of the data that has been collected, the authors obtain conclusions that can be drawn from the observations made regarding the Management Analysis of the Preparation of Work Plans in the Planning and Evaluation Section of the Sleman Regency Health Office D.I. Yogyakarta.Y where the Management of the preparation of the Work Plan carried out by the Sleman Regency Health Office is in accordance with the management theory and the work plan of the Sleman Regency Health Office in 2021 is in line with the Regional Head Regulation concerning the 2021 RKPD and based on the results of the evaluation of the 2021 Sleman Regency Health Office Renja will still be faced with several challenges caused by the Covid19 pandemic.